Summary of schemes for the assistance of the unemployable blind (1930)
1930 1930 1930s 6 pages 4. Gateshead. Augmented to 51 a week - single persons. Augmented to £1 10/- a week - man and wife both blind. Not eligible - Married blind women whose husbands are employed or employable; Shopkeepers; Inmates of Homes, Hostels, etc; Beggars. Board of Guardians in assessing relief for dependents to ignore the blind persons and the first 18/- of their income. Gloucester. Augmented to 16/- a week - single persons. Augmented to 26/- a week - married man with dependent wife. Must be over 21 years of age. Free lodgings, etc., taken into consideration. Halifax. Augmented to 18/- a week. Hastings. Augmented to £1 a week. Council contributes £200 per annum towards cost which is borne by voluntary association. Huddersfield. Augmented to £1 a week - non-householders. Augmented to 25/- a week - Householder. Awards are made irrespective of whether dependents or relatives can contribute towards the upkeep of the blind person or not. All blind persons are dealt with by the Local Authority. All dependents are dealt with by the Board of Guardians. Hull. Augmented to 11/6 a week - persons of 16 years of age. " " 13/6 a week - persons of 17 years of age. " " 16/- a week - persons of 18 years of age. " " 19/- a week - persons of 19 years of age. " " 22/- a week - persons of 20 years of age. " " 25/- a week - persons of 21 years or over. All blind persons dealt with by the local authority and not by Guardians. Leeds. Augmented to 15/- a week - single persons living with relatives. Augmented to 14/- plus rent a week - single persons living alone. Augmented to 13/- plus half the rent a week, married couple. Rent in every case up to a maximum of 6/- a week. Where there is need persons in receipt of Old Age Pensions an additional allowance of 2/6. above the scale of allowance. In determining income the following rules obtain :- Family - For children under 16, no earnings are taken into account. For sons between 16 - 21 years of age earnings over 17/6. a week taken into account. For daughters between 16 - 21 years of age earnings over 15/- a week taken into account. For sons over 21 years of age earnings over 25/- 292/841.4/1/40